Commingled nanocomposites of LDPE/PP/Nylon 6/EPDM reinforced with MWCNT and Kenaf Fiber with enhanced mechanical, thermal and flammability characteristics. (September 2015) - Khan, M. Ameen; Kumar, S. Satish; Raghu, T.S.; Kotresh, T.M.; Sailaja, R.R.N.
Graphical abstract: Highlights: Fire retardant commingled composites is developed. The mechanical properties improved by adding MWCNT and compatibilizers. Fire retatdancy also improved on MWCNT addition. The optimal MWCNT loading is 1.0% by weight. Abstract: Multicomponent commingled composites comprised of LDPE, PP, Nylon 6 and EPDM have been prepared using a mixture of two epoxy functionalized polyolefins as compatibilizers to enhance interfacial interactions. Kenaf fiber has also been added for reinforcement along with Multiwalled carbon nanotube (MWCNT). The mechanical and thermal properties for the nancomposites have been determined and assessed using predictive theories. The flammability characteristics for the nanocomposites were also assessed. The presence of MWCNT enhanced mechanical properties and also promoted char formation along with improved fire retardancy of the nanocomposites. These composites have potential for application as high performance fire retardant materials by recycling mixed plastic waste.